Flow Analysis in wavy pipes using Large Eddy Simulation - Menon, Sankar (My University, 2014)
Several types of heat exchangers are used in various industries depending on their applications and limitations. One of the most common arrangements for flow paths within a heat exchanger are counter- flow and parallel flow, which are manufactured at Tetra Pak Food Processing Unit, Lund. These long narrow pipes are given corrugation at the wall for enhanced efficiency. It was important to study and understand the flow and thermal distribution inside these pipes. In the current work, computation fluid dynamics (CFD) is used to understand and quantify these characteristics. Current work is based a Large Eddy Simulation of the flow where it is possible to resolve most of the eddies and less is modeled. In the current work, an in-house Chalmers solver, CALC-BFC is used for analysis. In the early stages of the thesis, it was important to validate the CALC solver and numerical methodologies. Thus the code is compared with the commercial software ANSYS Fluent and Star-CCM+. Later on, several refined meshes are simulated to realize how much is resolved and whether that is sufficient enough. Later on, study is done on the different implementations for the current problem and its repercussions is analysed. Once the code is validated enough, an attempt is given to understand the flow phenomenon and heat enhancement due to the corrugation given on the pipe. Finally, the height of the corrugation is varied, keeping the outer radius constant and results are presented.
Keywords: Energiteknik; Energi; Grundläggande vetenskaper; Hållbar utveckling; Strömningsmekanik och akustik; Energy Engineering; Energy; Basic Sciences; Sustainable Development; Fluid Mechanics and Acoustics